Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$(a+b)(c+d)=ac+ad+bc+bd$$ Why is this? Is there a proof to this? And there is something similar in logic.

$$(A \land B)\lor (C \land D)=(A \lor C)\land(A \lor D)\land(B \lor C)\land(B\lor D)$$ Why is this? I used it all my life but I don't know why it works.

share|improve this question
3  
The keyword here is "distributivity." See en.wikipedia.org/wiki/Distributive_property . –  Qiaochu Yuan Jul 16 '12 at 0:23
2  
Well, it depends on what number (logic?) system you're working in. But with many such systems - the integers, the rationals, the reals - you have a property called distributivity, which says that $(a+b)(c)$ = $ac + bc$. Apply this twice, and your identity holds in those number systems. –  user1296727 Jul 16 '12 at 0:23
    
The greeks had nice graphic proofs for such things. Look at this. –  phg Jul 16 '12 at 8:16
add comment

2 Answers

up vote 6 down vote accepted

It's called the distributive laws and the associative laws.

For numbers, addition and multiplication satisfy the following properties:

Associativity. For all $x,y,z$, $(x+y)+z = x+(y+z)$ and $(xy)z = x(yz)$.

Distributivity of $\times$ over $+$. For all $x,y,z$, $x(y+z) = (xy)+(xz)$ and $(y+z)x = (yx)+(zx)$.

These are properties that these operations satisfy. Not every operation does. for example, subtraction of numbers is not associative, and $+$ does not distribute over $\times$. Your first equation follows from the properties above: $$\begin{align*} (a+b)(c+d) &= (a(c+d)) + (b(c+d)) &&\text{(distributivity)}\\ &= \Bigl( (ac)+(ad)\Bigr) + \Bigl((bc) + (bd)\Bigr) &&\text{(distributivity twice)}\\ &= (ac)+(ad) + (bc)+ (bd) &&\text{(associativity allows the drop of parentheses)}\\ &= ac+ad+bc+bd &&\text{(precedence of operations: $\times$ goes before $+$)} \end{align*}$$

With logical connectives $\land$ (and) and $\lor$ (or), you have two distributive laws: $\land$ distributes over $\lor$: $$P\land(Q\lor S) = (P\land Q)\lor (P\land S)$$ and $\lor$ distributes over $\land$: $$P\lor(Q\land S) = (P\lor Q)\land (P\lor S).$$

So we have: $$\begin{align*} (A\land B)\lor (C\land D) &= (A\lor(C\land D)) \land (B\lor(C\land D))\\ &= (A\lor C)\land(A\lor D)\land (B\lor C)\land (B\lor D) \end{align*}$$

share|improve this answer
add comment

This is a consequence of the distributive property. We have that $$\begin{eqnarray} (a+b)(c+d) &=& a(c+d)+b(c+d)\\ &=& ac+ad+bc+bd \end{eqnarray}$$ thanks to left and right-distribution. A similar rule holds in logic, which is discussed in the Wikipedia page I linked to.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.